Structure and Membrane Targeting of the PDZD7 Harmonin Homology Domain (HHD) Associated With Hearing Loss - Lin, Lin; Wang, Huang; Ren, Decheng; Xia, Yitian; He, Guang; Lu, Qing (Frontiers in Cell and Developmental Biology, 2021)
Usher syndrome (USH) is the leading cause of hereditary hearing–vision loss in humans. PDZ domain-containing 7 (PDZD7) has been reported to be a modifier of and contributor to USH. PDZD7 co-localizes with USH2 proteins in the inner ear hair cells and is essential for ankle-link formation and stereocilia development. PDZD7 contains three PDZ domains and a low-complexity region between the last two PDZ domains, which has been overlooked in the previous studies. Here we characterized a well-folded harmonin homology domain (HHD) from the middle region and solved the PDZD7 HHD structure at the resolution of 1.49 Å. PDZD7 HHD adopts the same five-helix fold as other HHDs found in Harmonin and Whirlin; however, in PDZD7 HHD, a unique α1N helix occupies the canonical binding pocket, suggesting a distinct binding mode. Moreover, we found that the PDZD7 HHD domain can bind lipid and mediate the localization of PDZD7 to the plasma membrane in HEK293T cells. Intriguingly, a hearing-loss mutation at the N-terminal extension region of the HHD can disrupt the lipid-binding ability of PDZD7 HHD, suggesting that HHD-mediated membrane targeting is required for the hearing process. This structural and biochemical characterization of the PDZD7 HHD region provides mechanistic explanations for human deafness-causing mutations in PDZD7. Furthermore, this structure will also facilitate biochemical and functional studies of other HHDs.